Investigating the Role of the Primary Motor Cortex in Musical Creativity: A Transcranial Direct Current Stimulation Study - Anic, Aydin; Olsen, Kirk N.; Thompson, William Forde (Frontiers in Psychology, 2018)
Neuroscientific research has revealed interconnected brain networks implicated in musical creativity, such as the executive control network, the default mode network, and premotor cortices. The present study employed brain stimulation to evaluate the role of the primary motor cortex (M1) in creative and technically fluent jazz piano improvisations. We implemented transcranial direct current stimulation (tDCS) to alter the neural activation patterns of the left hemispheric M1 whilst pianists performed improvisations with their right hand. Two groups of expert jazz pianists (n = 8 per group) performed five improvisations in each of two blocks. In Block 1, they improvised in the absence of brain stimulation. In Block 2, one group received inhibitory tDCS and the second group received excitatory tDCS while performing five new improvisations. Three independent expert-musicians judged the 160 performances on creativity and technical fluency using a 10-point Likert scale. As the M1 is involved in the acquisition and consolidation of motor skills and the control of hand orientation and velocity, we predicted that excitatory tDCS would increase the quality of improvisations relative to inhibitory tDCS. Indeed, improvisations under conditions of excitatory tDCS were rated as significantly more creative than those under conditions of inhibitory tDCS. A music analysis indicated that excitatory tDCS elicited improvisations with greater pitch range and number/variety of notes. Ratings of technical fluency did not differ significantly between tDCS groups. We discuss plausible mechanisms by which the M1 region contributes to musical creativity.